The Universal Value of Islam as Rahmatan Lil 'Alamin - Abdulloh Safiq; M. Miftakhul Huda; Abdul Khamid (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
The scholars have determined that Islamic law has an eternal maqashid (goal) to preserve human intelligence, offspring, property, religion and self-esteem, because Islam never teaches enmity or hatred. This is where the term